2013
DOI: 10.1007/s00709-013-0564-1
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast molecular farming: efficient production of a thermostable xylanase by Nicotiana tabacum plants and long-term conservation of the recombinant enzyme

Abstract: The high cost of recombinant enzymes for the production of biofuel from ligno-cellulosic biomass is a crucial factor affecting the economic sustainability of the process. The use of plants as biofactories for the production of the suitable recombinant enzymes might be an alternative to microbial fermentation. In the case of enzyme accumulation in chloroplasts, it is fundamental to focus on the issue of full photosynthetic efficiency of transplastomic plants in the field where they might be exposed to abiotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…CelK1 leaf extract was used in combination with a homogenate obtained from either a previously described line overexpressing a thermostable xylanase (BSX) [15, 18] or a Pga2 transformed line. Since the final protein concentration in each assay was 0.1 mg/mL, the amount of reducing sugars released from poplar wood when assayed at pH 7 with a mixture of CelK1 and BSX was synergistic as compared to the action of each enzyme alone (Figure 6(a)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CelK1 leaf extract was used in combination with a homogenate obtained from either a previously described line overexpressing a thermostable xylanase (BSX) [15, 18] or a Pga2 transformed line. Since the final protein concentration in each assay was 0.1 mg/mL, the amount of reducing sugars released from poplar wood when assayed at pH 7 with a mixture of CelK1 and BSX was synergistic as compared to the action of each enzyme alone (Figure 6(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes used for industrial applications, among which biofuel production is found, are currently produced via microbial fermentation even if the process requires high investment, production, and maintenance costs. Several studies show that protein/enzyme production by plant molecular farming might offer some advantages over microorganisms, as plants have both eukaryotic (nuclear) and prokaryotic (chloroplast) expression systems [1518] that can be used singly or in combination. Transgenic plants were shown to be a valuable system for the production of a variety of antibodies, proteins/enzymes, and vaccines [19].…”
Section: Introductionmentioning
confidence: 99%
“…The development of chloroplast derived cocktails of enzymes for production of fermentable sugars from different ligno-cellulosic biomass become major fresh breakthrough in biofuels research. Different enzymes from bacteria or fungi, namely β - 1,4 - endoglucanase , Beta glucosidase, Swollenin, esterase , cutinase , endoglucanases , exoglucanase , pectate lyases , xylanase , lipase , acetyl , Acetyl xylan esterase and xylan were expressed in tobacco chloroplasts for production of fermentable sugars [107111]. …”
Section: Introductionmentioning
confidence: 99%
“…β-Mannanase enzyme from Trichoderma reesei showed sixfold to sevenfold higher enzyme activity than E. coli . β-Mannanase enzyme cocktail with chloroplast derived mannanse yielded 20% more glucose equivalents from pinewood than the cocktail without mannanase [111]. Catalytic activity of chloroplast produced Xylanase was detected with birch wood xylan as substrate [112].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, chloroplast metabolic engineering is used to synthesize low-cost enzyme cocktails for biomass hydrolysis and especially for the digestion of lignocellulosic biomass in order to generate fermentable sugars for ethanol production. However, the stability of the recombinant enzymes under variable field conditions, e.g., abiotic stressors, such as light, temperature, etc., as well as during extraction and storage also has to be maintained (Pantaleoni et al 2014). An example for bioplastic production is the introduction of complex metabolic pathways such as polyhydroxybutyrate (PHB) synthesis into the plastids (Nakashita et al 2001;Lössl et al 2003Lössl et al , 2005.…”
Section: Molecular Pharming-accumulation Of Recombinant Proteinsmentioning
confidence: 99%